The quality of the Zygmunt Spring water (southern Poland) – preliminary results - Dąbrowska, Dominika; Ruman, Marek; Wróbel, Jacek (Quaestiones Geographicae, 2024)
Natural springs are one of the potential sources of water supply, but due to negative anthropogenic impacts, the water quality can deteriorate. The Zygmunt Spring in Złoty Potok does not form the basis of the population’s water supply, but it is constantly being exploited by residents and tourists. This study was carried out at Zygmunt Spring in two measurement series for 34 physicochemical and bacteriological parameters. The average electrolytic conductivity (EC) of the water in this spring is about 0.039 S ∙ m−1, the pH is about 7.04 and the discharge is equal to 15 dm3 ∙ s−1. The test results were compared with the permissible limits for national drinking water, groundwater quality and WHO standards. The value of the Backman pollution index was calculated for these parameters. This index takes into account parameters that exceed the upper permissible concentrations of contaminants. The Backman Contamination Index value was about −13, but the results of bacteriological analyses indicate a very high number of microorganisms in the water (>300 cfu ∙ mL−1), indicating a high health risk.